2021
DOI: 10.1186/s13049-021-00837-x
|View full text |Cite
|
Sign up to set email alerts
|

Association between the body mass index and outcomes of patients resuscitated from out-of-hospital cardiac arrest: a prospective multicentre registry study

Abstract: Background The effects of the body mass index (BMI) on outcomes of patients resuscitated from cardiac arrest are controversial. Therefore, the current study investigated the association between the BMI and the favourable neurologic outcomes and survival to discharge of patients resuscitated from out-of-hospital cardiac arrest (OHCA). Methods This multicentre, prospective, nationwide OHCA registry-based study was conducted using data from the Korean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 25 publications
(34 reference statements)
0
12
0
Order By: Relevance
“…However, no study was found to investigate the effect of the patient's place of living on the cardiopulmonary resuscitation. Another study showed that the body mass index is not independently associated with the patient's survival rate [31]. This quantitative study investigated the output of the cardiopulmonary resuscitation, and its setting and research method are different from the current study.…”
Section: Discussionmentioning
confidence: 66%
“…However, no study was found to investigate the effect of the patient's place of living on the cardiopulmonary resuscitation. Another study showed that the body mass index is not independently associated with the patient's survival rate [31]. This quantitative study investigated the output of the cardiopulmonary resuscitation, and its setting and research method are different from the current study.…”
Section: Discussionmentioning
confidence: 66%
“…Malnutrition and baseline comorbidities, which can cause a patient to be underweight, may increase the risk of poor outcomes. Additionally, underweight cardiac arrest patients less frequently showed cardiogenic arrest with shockable rhythms, which is a good prognostic factor for the etiology of cardiac arrest [13,17].…”
Section: Discussionmentioning
confidence: 99%
“…After reviewing the full-text articles more thoroughly, we excluded 43 studies for irrelevant population (n = 25), irrelevant outcome measure (n = 12), irrelevant control group (n = 4), and meta-analyses (n = 2). The six remaining studies with 2427 patients were included in the meta-analysis [13,17,18,[25][26][27]. The reference management software, Endnote X9 (Clarivate Analytics, Philadelphia, United States), was used for all identified studies in the literature search.…”
Section: Study Selectionmentioning
confidence: 99%
See 2 more Smart Citations